Leveraging Trust as an Intermediary Construct for Enhancing Public Acceptance of Smart Government Model - Mohammed Thaiban, Hamdan Hasan; Sidek, Safiah (International Journal of Sustainable Construction Engineering and Technology, 2023)
The primary aim of this study was to formulate a trust model aimed at augmenting public acceptance of UAE's smart government services. The study identified a total of 31 factors categorized into seven distinct groups or constructs. The model comprises five independent constructs which are Word of Mouth, Knowledge and Experience, IT Quality, Privacy, and Security. Then, Trust as an intermediary construct while Acceptance as a dependent construct. Through a convenience sampling approach, data was collected from 400 respondents via a questionnaire survey. The data collected was utilized to create and refine the model using SmartPLS software. The model underwent thorough analysis, including assessments of convergent reliability and validity, discriminant validity, and hypothesis testing. The study results revealed the significance of all six hypotheses, indicating the noteworthy impact of the five independent constructs on the intermediary construct (Trust), which in turn significantly influences the dependent construct (Acceptance). In terms of its contribution to existing knowledge, this study significantly enriches the literature on citizen-centric models and smart government. Moreover, in practical terms, the findings provide valuable insights for policy makers and smart government officials to strategically optimize approaches, thereby facilitating the expedited and more effective adoption of smart government services.